Sodium butyrate suppresses NOD1‐mediated inflammatory molecules expressed in bovine hepatocytes during iE‐DAP and LPS treatment. Issue 11 (2nd April 2019) - Roy, Animesh Chandra; Chang, Guangjun; Ma, Nana; Wang, Yan; Roy, Shipra; Liu, Jing; Aabdin, Zain‐Ul; Shen, Xiangzhen
Abstract: Nucleotide oligomerization domain protein‐1 (NOD1), a cytosolic pattern recognition receptor for the γ‐D‐glutamyl‐ meso ‐diaminopimelic acid (iE‐DAP) is associated with the inflammatory diseases. Very little is known how bovine hepatocytes respond to specific ligands of NOD1 and sodium butyrate (SB). Therefore, the aim of our study was to investigate the role of bovine hepatocytes in NOD1‐mediated inflammation during iE‐DAP or LPS treatment or SB pretreatment. To achieve this aim, hepatocytes separated from cows at ∼160 days in milk (DIM) were divided into six groups: The nontreated control group (CON), the iE‐DAP‐treated group (DAP), the lipopolysaccharide‐treated group (LPS), iE‐DAP with SB group (DSB), LPS with SB group (LSB), and the SB group. Both iE‐DAP and LPS highly increased the expression of both NOD1 and RIPK2, the two key factors for the immune response in hepatocytes. IκBα, NF‐κB/p65, and MAP kinases (ERK, JNK, and p38) were activated through phosphorylation. The activation of NF‐κB and MAPK pathway consequently increased the proinflammatory cytokines, IL‐6, TNF‐α, IL‐8, and IFN‐γ and the chemokines CCL5, CCL20, and CXCL‐10. Both treatments improved iNOS/NOS2 expression. However, iE‐DAP was failed to express acute phase protein SAA3, but HP and LPS HP but SAA3. These ligands also increased LRRK2, TAK1, TAB1, and β‐defensins expression. The SB pretreatment at lower dose restored the function of hepatocytes by suppressing these increased molecules, as HDAC3 was inhibited. The activated NOD1 negatively regulated the expression of FOXA2. Altogether these data suggest an important role of bovine hepatocytes to promote immune responses via NOD1 expression during infection in the liver and a key role of SB to attenuate inflammation. Abstract : The results suggest an important role of bovine hepatocytes to promote immune responses via NOD1 expression during infection in the liver and a key role of SB to attenuate inflammation.